2022
DOI: 10.3390/su14020724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Value Perception on Farmers’ Willingness to Participate in Farmland Fallow: A Case-Study in Major Grain-Producing Areas of Hubei and Hunan, China

Abstract: The major grain-producing areas will be the key areas of future China fallow. It is important to explore the influence of farmers’ value perceptions on their fallow willingness in these areas. We analyzed this impact of value perception by using an ordered PROBIT model and survey data from the major grain-producing areas of Hubei and Hunan, China. The conclusions of this study are as follows: (1) A considerable proportion of farmers are willing to participate in farmland fallow, while a considerable proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…This implies that local community members will actively participate in all stages of sustainable mangrove forest management if they can perceive the value of mangrove ecosystem services. This finding is in line with Zhang et al's [104] study, which revealed that farmers' perceived values of farmland significantly affected their participation in ecological environmental protection on farmland. Similarly, Hernes and Metzger [114] showed that the active participation of stakeholders in biosphere management and conservation activities was significantly affected by stakeholders' perceived environmental values, such as wildlife values and the beauty of nature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This implies that local community members will actively participate in all stages of sustainable mangrove forest management if they can perceive the value of mangrove ecosystem services. This finding is in line with Zhang et al's [104] study, which revealed that farmers' perceived values of farmland significantly affected their participation in ecological environmental protection on farmland. Similarly, Hernes and Metzger [114] showed that the active participation of stakeholders in biosphere management and conservation activities was significantly affected by stakeholders' perceived environmental values, such as wildlife values and the beauty of nature.…”
Section: Discussionsupporting
confidence: 90%
“…These services could potentially contribute to both the improvement of human well-being and the socio-economic development of a society. Many scholars have explored people's perceptions of the ecological values of a natural resource based on the ecosystem services it provides [101][102][103][104]. This study also measured participants' perceptions of the ecological values provided by a mangrove forest based on subjective valuation.…”
Section: • Perceived Values Of the Csr Project (Perception Of Ecologi...mentioning
confidence: 99%
“…Secondly, it is supposed to vigorously promote land transfer and strengthen machinery input, so as to improve grain production efficiency and profit. Third, many studies advocate that grain subsidies should be increased to make grain growing truly profitable for farmers [ 61 , 63 ]. Fourth, fostering diversified grain production subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers' value perception is their weighing of costs and benefits before making behavioral decisions [31,32]. Farmers' adoption of new technologies is related to how the technology is disseminated and their value perceptions of the new technology [33].…”
Section: The Mediating Role Of Value Perceptionmentioning
confidence: 99%